IEEE Africon '11 2011
DOI: 10.1109/afrcon.2011.6072084
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical outlines for OLPC initiatives: A case of Ukombozi school in Tanzania

Abstract: One-to-one computing initiatives in developing countries have been criticized for ignoring pedagogical considerations and for lacking tight integration with the local educational context. Ukombozi primary school in Iringa, Tanzania, faced the same situation in 2009, when we received 100 laptop computers for pupils to use. Through a collaborative effort of local and foreign teachers we designed and tested a pedagogical approach which starts from the local educational context, and builds on theoretical literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…Content Apiola et al (2011) Field-level experiences of OLPC use from a Tanzanian school de Macedo Guimarães et al (2013) Field-level experiences of OLPC use from Brazilian schools Duveskog et al (2010) Field-level experiences of OLPC use from a Tanzanian school Gyabak and Godina (2011) Field-level experiences of OLPC use from a Bhutanese school Hartel (2008) OLPC implementation in Ethiopia Hirji et al (2010) Consolidated report of evaluations from different OLPC country sites presenting field-level observations and case studies Hourcade et al (2008) Field-level experiences of OLPC use from a Uruguayan school Mary and Bassi (2008) Various regional OLPC case studies Following collation of the text from the sources identified, it was filtered in order to perform template analysis (Cassell and Symon, 2004;King, 2007). The first step of the analysis was identification of user and intermediary stakeholder groups, following the argument presented in Section 4.2.…”
Section: Sourcementioning
confidence: 99%
“…Content Apiola et al (2011) Field-level experiences of OLPC use from a Tanzanian school de Macedo Guimarães et al (2013) Field-level experiences of OLPC use from Brazilian schools Duveskog et al (2010) Field-level experiences of OLPC use from a Tanzanian school Gyabak and Godina (2011) Field-level experiences of OLPC use from a Bhutanese school Hartel (2008) OLPC implementation in Ethiopia Hirji et al (2010) Consolidated report of evaluations from different OLPC country sites presenting field-level observations and case studies Hourcade et al (2008) Field-level experiences of OLPC use from a Uruguayan school Mary and Bassi (2008) Various regional OLPC case studies Following collation of the text from the sources identified, it was filtered in order to perform template analysis (Cassell and Symon, 2004;King, 2007). The first step of the analysis was identification of user and intermediary stakeholder groups, following the argument presented in Section 4.2.…”
Section: Sourcementioning
confidence: 99%
“…The aim was divided into two objectives: 1) to characterize 978-1-4673-5943-6/13/$31.00 c 2013 IEEE TABLE I. CLASSROOM MODEL [14] Component…”
Section: Research Questionsmentioning
confidence: 99%
“…The main theoretical background was based on the self-determination theory (SDT) [11], on supporting constructionism and constructivism by utilizing ideas by Seymour Papert [12], and on ideas extracted from the cognitive flexibility theory [13]. That pedagogical framework [14] is presented in Table I.…”
Section: Constructivismmentioning
confidence: 99%
See 2 more Smart Citations